The mnonic writing in Malika Mokeddem’s N’zid as a process of (re)construction identity (مجلة الواحات للبحوث والدراسات, 2020)
Lost between the two shores of the Mediterranean, after surviving an attack of which she ignores the author, Malika Mokeddem’s heroine in his novel N’zid is desperate to reconnect with his origins.This wandering seems to be a deconstruction for (re) construction. It is for this amnesiac person to be (re) make again an identity where it would be possible from him to be reconciled with all the features composing his being.In her text, the writer emphasizes the fusion of multiple and diverse cultural fragments within the ego. Through the quest of the hero Nora, she advocates the miscegenation of identity and tends towards universal belonging.KEYWORDS -identity - otherness - fragments - boundaries – interbreeding